Transperineal Ultrasound for Perianal Fistulas and Abscesses – A Systematic Review and Meta-Analysis - Maconi, Giovanni; Greco, Maria Teresa; Asthana, Anil Kumar (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose Transperineal ultrasound (TPUS) is a practical tool for assessing perianal inflammatory lesions. We systematically review its accuracy for detecting and classifying perianal fistulae and abscesses.Method The National Library of Medicine and Embase were searched for articles on TPUS for the assessment of idiopathic and Crohn’s perianal fistulae and abscesses. Two reviewers independently reviewed eligible studies and rated them for quality using the QUADAS tool. The primary outcome measure was the accuracy of TPUS as measured by its sensitivity and positive predictive value (PPV) in detecting and classifying perianal fistulae, internal openings and perianal abscesses.Results We included 12 studies (565 patients). Overall, the methodological quality of the studies was suboptimal. 3 studies were retrospective and 4 showed significant risks of bias in the application of the reference standard. The sensitivity of TPUS in detecting perianal fistulae on a per-lesion basis was 98 % (95 % CI 96 – 100 %) and the PPV was 95 % (95 % CI 90 – 98 %). The detection of internal openings had a sensitivity of 91 % (95 % CI 84 – 97 %) with a PPV of 87 % (95 % CI 76 – 95 %). The classification of fistulae yielded a sensitivity of 92 % (95 % CI 85 – 97 %) and a PPV of 92 % (95 % CI 83 – 98 %). TPUS had a sensitivity of 86 % (95 % CI 67 – 99 %) and PPV of 90 % (95 % CI 76 – 99 %) in the detection of perianal abscesses.Conclusion The current literature on TPUS illustrates good overall accuracy in the assessment of perianal fistulae and abscesses. However, many studies had methodological flaws suggesting that further research is required.
Keywords: anus; fistula; abscess; perianal; ultrasound; meta-analysis